A competitive binding-mass spectrometry strategy for high-throughput evaluation of potential critical quality attributes of therapeutic monoclonal antibodies. Issue 1 (31st December 2022) - Zhang, Zhengqi; Yan, Yuetian; Wang, Shunhai; Li, Ning
ABSTRACT: Therapeutic monoclonal antibodies (mAbs) have a propensity to host a large number of chemical and enzymatical modifications that need to be properly assessed for their potential impact on target binding. Traditional strategies of assessing the criticality of these attributes often involve a laborious and low-throughput variant enrichment step prior to binding affinity measurement. Here, we developed a novel competitive binding-based enrichment strategy followed by mass spectrometry analysis (namely, competitive binding-MS) to achieve high-throughput evaluation of potential critical quality attributes in therapeutic mAbs. Leveraging the differences in target binding capability under competitive binding conditions, the criticality of multiple mAb attributes can be simultaneously evaluated by quantitative mass spectrometry analysis. The utility of this new workflow was demonstrated in three mAb case studies, where different post-translational modifications occurring within the complementarity-determining regions were successfully interrogated for their impact on antigen binding. As this workflow does not require prior enrichment (e.g., by forced degradation or liquid chromatography fractionation) of the variants, it is particularly valuable during the mAb candidate developability assessment, where fast turn-around time is highly desired to assist candidate selection. Abbreviations : ACN: acetonitrile; ADCC: antibody-dependent cell-mediated cytotoxicity; AEX: anion exchange chromatography; bsAb: bispecific antibody; CDC: complement-dependent cytotoxicity; CDR: complementarity-determining region; CML: carboxymethylation; CQA: critical quality attribute; DDA: data-dependent acquisition; DMSO: dimethyl sulfoxide; DTT: dithiothreitol; FA: formic acid; Fab: Fragment antigen-binding; FcRn: neonatal Fc receptor; HC: heavy chain; HIC: hydrophobic interaction chromatography; IAA: iodoacetamide; IEX: ion exchange chromatography; LC: light chain; mAb monoclonal antibody; msAb: monospecific antibody; MS: mass spectrometry; PBS: phosphate-buffered saline; pI: isoelectric point; PTM: post-translational modification; SCX: strong cation exchange chromatography; SEC: size exclusion chromatography; SPR: surface plasmon resonance; XIC: extracted ion chromatography.